Adult Mental Health Outpatients Who Have Minor Children: Prevalence of Parents, Referrals of Their Children, and Patient Characteristics - Ruud, Torleif; Maybery, Darryl; Reupert, Andrea; Weimand, Bente; Foster, Kim; Grant, Anne; Skogøy, Bjørg Eva; Ose, Solveig O. (Frontiers in Psychiatry, 2019)
Background: A strong connection exists between parental mental illness and lifetime mental health risk for their children. Thus, it is important to determine, when parents attend for treatment for their illness, the prevalence and characteristics of parents with a mental illness and identify referral actions for their children. Previous studies indicate that 12–45% of adult mental health service patients are parents with minor children. There is a need for studies with larger sample sizes that investigate the prevalence and characteristics of parents, and factors associated with referral actions for their children. Method: Data on 23,167 outpatients was drawn from a national census study across 107 Norwegian adult mental health outpatient clinics during 2 weeks in April 2013. Clinicians identified various socio-demographic characteristics of patients who were parents and referral actions for their children. Results: Eight thousand thirty-five (36%) of outpatients had children under 18 years. Thirty-one percent were provided with referrals for their children and 58% were reported to have children with no need for referral. Three percent were reported to have children with unmet needs who were not referred. There were missing data on children's needs and referral actions for 8% of parents. Patients who care for minor children were more likely to be refugees, and less likely to be single, male, not own a house/apartment, and have a schizophrenia spectrum illness or substance use disorder. Children were more likely to be referred when their parent was single, with no income from paid work, low education, not owning house/apartment, poor family network, long outpatient treatment, and an individual care plan; and less likely for men with a moderate or less severe mental illness. Children were referred to child protection agencies, child and adolescent mental health services and school psychological/pedagogic services. Discussion: The prevalence of outpatients with children is similar to other studies. Referrals were made for children of one third of outpatients with minor children. Needs and referrals of children was unknown for one in ten outpatients. Mental health outpatient clinics must improve procedures to identify parenting status and ascertain and act on children's needs.